Hybrid Lymphovenous Anastomosis Surgery Guided by Intraoperative Mesenteric Intranodal Lymphangiography for Refractory Nontraumatic Chylous Ascites: A Case Report - Woo, Soo Jin; Hur, Saebeom; Kim, Hee Seung; Chang, Hak; Kim, Ji-Young; Park, Soo Jin; Jin, Ung Sik (Archives of Plastic Surgery, 2024)
Refractory chylous ascites can cause significant nutritional and immunologic morbidity, but no clear treatment has been established. This article introduces a case of a 22-year-old female patient with an underlying lymphatic anomaly who presented with refractory chylous ascites after laparoscopic adnexectomy for ovarian teratoma which aggravated after thoracic duct embolization. Ascites (>3,000 mL/d) had to be drained via a percutaneous catheter to relieve abdominal distention and consequent dyspnea, leading to significant cachexia and weight loss. Two sessions of hybrid lymphovenous anastomosis (LVA) surgery with intraoperative mesenteric lymphangiography guidance were performed to decompress the lymphatics. The first LVA was done between inferior mesenteric vein and left para-aortic enlarged lymphatics in a side-to-side manner. The daily drainage of chylous ascites significantly decreased to 130 mL/day immediately following surgery but increased 6 days later. An additional LVA was performed between right ovarian vein and enlarged lymphatics in aortocaval area in side-to-side and end-to-side manner. The chylous ascites resolved subsequently without any complications, and the patient was discharged after 2 weeks. The patient regained weight without ascites recurrence after 22 months of follow-up. This case shares a successful experience of treating refractory chylous ascites with lymphatic anomaly through LVA, reversing the patient's life-threatening weight loss. LVA was applied with a multidisciplinary approach using intraoperative mesenteric lipiodol, and results showed the possibility of expanding its use to challenging problems in the intraperitoneal cavity.
Keywords: chylous ascites; lymphangiography; lymphovenous anastomosis